Penguatan Kompetensi Teologis Katekis Pemula: Program Pembinaan Credo untuk Pewartaan Iman di Paroki Santo Krisologus BSB - Sugiyana Sugiyana; Anselmus Joko Prayitno; Nerita Setyaningtyas (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
This community service program aimed to enhance the theological competence of novice catechists and community guides at Santo Krisologus BSB Parish Semarang, focusing on understanding and articulating Catholic Fundamental Beliefs, particularly the Credo. Based on observations from January-August 2024, a gap was identified between high enthusiasm for service and the competency readiness of novice faith proclaimers. The program employed an integrative methodological approach combining interactive lectures, question-and-answer sessions, and participatory observation, accompanied by multi-stage evaluation. Results showed significant improvements in participants' doctrinal understanding and pedagogical abilities, reflected in the quality of theological discussions and the formation of sustainable learning communities. The main challenge identified was the complexity of articulating Trinitarian dogma in contemporary pastoral contexts. This program produced a replicable catechist formation model while affirming the importance of an integrative approach in faith proclaimer development.